The impacts of Muslim funerary practices to the urban heat island (UHI) in metropolitan regions of Malaysia - Rosli, Farhana Nur Izati; Sanusi, Aliyah Nur Zafirah; Alias, Nur Ulfah Awatif Umairah; Ismail, Mohd Noorizhar; Abdullah, Fadzidah (IFERP Explore, 2023)
Burial grounds, also known as cemeteries, are places where the living honour and remember the death of their loved ones. While some may disagree, cemeteries continue to play an important role in our modern society. Cemeteries are often interfered with a region's cultural and religious traditions. As such, it can be varied in size and funeral rites. This paper examines issues and problems under three different aspects which are the aspect of policy, culture and environment that takes place in the metropolitan regions of Malaysia, specifically, within Kuala Lumpur. The objectives of this paper are; to identify true fundamental guidelines of a Muslim funerary practice according to the governance of Islam and to measure the impacts of hard surfaces found in urban cemeteries towards the surrounding UHI. Fieldwork was conducted to analyze the air temperature differences of different urban cemeteries with their percentages of grass covers. The sites take place in Tanah Perkuburan Jalan Ampang (Site A and B) and Tanah Perkuburan Jalan Kuari, Cheras (Site C). Significant findings in this paper conclude that cemetery ground with 55.8% grass cover recorded a 2°C lower maximum dry bulb temperature than the cemetery ground with 17.2% grass cover.